DEVELOPMENT OF A CAREER COUNSELING MODEL TO ADDRESS THE DILEMMA OF PRESTIGE AND EMPLOYMENT DECISIONS OF BACHELOR'S DEGREE GRADUATES - Hafifah, Nur; Muarif, Ahmad Syamsul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The phenomenon of the